Determinants of exercise adherence in sedentary middle‐aged and older adults - Cabral, Danylo F.; Fried, Peter J.; Bigliassi, Marcelo; Cahalin, Lawrence P.; Gomes‐Osman, Joyce (Psychophysiology, 2024)
Regular exercise positively impacts neurocognitive health, particularly in aging individuals. However, low adherence, particularly among older adults, hinders the adoption of exercise routines. While brain plasticity mechanisms largely support the cognitive benefits of exercise, the link between physiological and behavioral factors influencing exercise adherence remains unclear. This study aimed to explore this association in sedentary middle‐aged and older adults. Thirty‐one participants underwent an evaluation of cortico‐motor plasticity using transcranial magnetic stimulation (TMS) to measure changes in motor‐evoked potentials following intermittent theta‐burst stimulation (iTBS). Health history, cardiorespiratory fitness, and exercise‐related behavioral factors were also assessed. The participants engaged in a 2‐month supervised aerobic exercise program, attending sessions three times a week for 60 min each, totaling 24 sessions at a moderate‐to‐vigorous intensity. They were divided into Completers (n = 19), who attended all sessions, and Dropouts (n = 12), who withdrew early. Completers exhibited lower smoking rates, exercise barriers, and resting heart rates compared to Dropouts. For Completers, TMS/iTBS cortico‐motor plasticity was associated with better exercise adherence (r = −.53, corrected p = .019). Exploratory hypothesis‐generating regression analysis suggested that post‐iTBS changes (β = −7.78, p = .013) and self‐efficacy (β = −.51, p = .019) may predict exercise adherence (adjusted‐R2 = .44). In conclusion, this study highlights the significance of TMS/iTBS cortico‐motor plasticity, self‐efficacy, and cardiovascular health in exercise adherence. Given the well‐established cognitive benefits of exercise, addressing sedentary behavior and enhancing self‐efficacy are crucial for promoting adherence and optimizing brain health. Clinicians and researchers should prioritize assessing these variables to improve the effectiveness of exercise programs. Adherence to exercise and its cognitive brain health benefits relies on the mechanism of neuroplasticity, which may be altered by sedentariness and lack of self‐efficacy in middle‐aged and older adults. This study provides a better understanding of the link between physiological TMS/iTBS cortico‐motor plasticity and exercise‐related behavioral measures, which may advance current evidence and allow therapists and researchers to optimize and tailor exercise interventions for cognitive brain health.